Mathematical modelling of a 100m sprint - Lam, Chun Hong (2019)
The 100m sprint is a common event in competitive Track and Field. It is one of the most popular and prestigious event in the sport of athletics. Athletes usually accelerate out of the blocks and reach top speed at around the midway point of the race (50m). Then they try to maintain their top speed for as long as possible before they progressively decelerate in the later stages of the race. Hence we can characterise the run by 2 distinct parts: acceleration and deceleration. It is possible to use exponential functions to model it. In fact there are already some existing models out there to model the performance of elite athletes. However, there are no mathematical models that are catered for recreational athletes and as for the existing models, they do not provide much insights as to what physiological factors affect the athlete’s run performance. The purpose of this project is to develop a mathematical model for recreational athletes, with the aid of MATLAB programming and to infer and interpret the physical meanings of the constants and factors in the model that affects the athlete’s 100m run performance.